Dysglycemia and increased left ventricle mass in normotensive patients admitted with a first myocardial infarction: prognostic implications of dysglycemia during 14 years of follow-up - Gokulan Pararajasingam; Brian Bridal Løgstrup; Dan Eik Høfsten; Thomas Brøcher Christophersen; Søren Auscher; Jørgen Hangaard; Kenneth Egstrup (BMC Cardiovascular Disorders, 2019)
Abstract Background Left ventricle mass (LVM) can be influenced by various conditions including hypertension and/or inherent cardiomyopathies. Dysglycemia is also thought to exert an anabolic effect on heart tissue by hyperinsulinemia and thereby promoting increased LVM. The primary aim of this study was to assess the influence of dysglycemia on LVM evaluated by an oral glucose tolerance test (OGTT) in patients admitted with a first myocardial infarction (MI) without hypertension. The secondary aim was to assess the impact of dysglycemia on major adverse cardiovascular events (MACE) and all-cause mortality during long-term follow-up. Methods Patients admitted with a first MI without known history of hypertension were included. All patients without previously known type 2 diabetes mellitus (T2DM) had a standardized 2-hour OGTT performed and were categorized as: normal glucose tolerance (NGT), impaired fasting glucose (IFG)/impaired glucose tolerance (IGT) and newly detected T2DM (new T2DM). LVM was measured by echocardiography using Devereaux formula and indexed by body surface area. Multivariate linear regression analysis was used to assess the impact of confounders (dysglycemia by OGTT, known T2DM, age, sex and type of MI) on LVM. Cox proportional hazard model was used to assess the impact of dysglycemia on all-cause mortality and a composite endpoint of MACE (all-cause mortality, MI, revascularisation due to stable angina, coronary artery bypass graft, ischemic stroke or hemorrhagic stroke). Results Two-hundred-and-five patients were included and followed up to 14 years. In multivariate regression analysis, LVM was only significantly increased in patients categorized as new T2DM (β = 25.3; 95% CI [7.5–43.0]) and known T2DM (β = 37.3; 95% CI [10.0-64.5]) compared to patients with NGT. Patients with new T2DM showed higher rates of MACE and all-cause mortality compared to patients with IFG/IGT and NGT; however no significantly increased hazard ratio was detected. Conclusions Dysglycemia is associated with increasing LVM in normotensive patients with a first acute myocardial infarction and the strongest association was observed in patients with new T2DM and patients with known T2DM. Dysglycemia in normotensive patients with a first MI is not an independent predictor of neither MACE nor all-cause mortality during long-term follow-up compared to normotensive patients without dysglycemia.